The Influence of Problem-Based Explorative Learning Model (PEM) in Increasing Students' Ability to Create Solutions to Environmental Problems - Zahratush Shalehah; Siti Alimah (Universitas Negeri Semarang, 2024)
Learning about environmental issues has not been carried out well, the environment around the school is not utilized optimally. Problems in the environment around the school can be used as a learning resource to improve students' thinking abilities in creating solutions. Students gain meaningful learning experiences through problem-based exploratory learning in the environment around the school. The research aims to analyze the effect of applying the Problem-based Explorative Learning Model (PEM) in learning environmental problems on increasing students' ability to create solutions. This research uses a pre-experimental design, one group pretest-posttest design. Samples were taken using random sampling technique. Data was collected through observation sheet instruments, essay test questions, student response reflection journals and biology teacher responses. The effect of the PEM model was measured using the Paired Sample T-test with a Sig (2-tailed) value of 0.000 <0.05 and an N-gain score indicating a Sig value. 0.76>0.7. The results show that there are differences in pretest-posttest scores on the variable ability to create solutions and a significant influence on the application of the PEM Model in learning environmental problems. Achievement of the Ability to Create Solutions (KMS) indicator shows an average score of 82%. The implementation of the PEM Model syntax was measured using a student response instrument with an average score of 87% and a biology teacher response instrument with an average score of 94%. The implementation of learning using the PEM Model was very good. In conclusion, the PEM model has a significant effect in increasing students' ability to create solutions to learning environmental problems.